A Novel Three-Dimensional Platform to Investigate Neoangiogenesis, Transendothelial Migration, and Metastasis of MDAMB-231 Breast Cancer Cells. Issue 3 (September 2016) - Hooper, Rachel C.; Jacoby, Adam; Asanbe, Ope; Osoria, Hector L.; Morrison, Kerry A.; Hernandez, Karina; Boyko, Tatiana; Joyce, Jeremiah; Landford, Wilminia; Spector, Jason A.
Abstract : Background: A crucial step in the progression of cancer involves the transendothelial migration of tumor cells into the bloodstream and invasion at distant sites. Most in vitro models of malignant cell behavior do not account for the presence of and interaction with vascular cells. Three-dimensional platforms to further explore the factors responsible for metastatic cellular behavior are under intensive investigation. Methods: Hydrogels with encapsulated MDAMB-231 breast cancer cells were fabricated with a central microchannel. The microchannel was lined with a co-culture of human umbilical vein endothelial cells and human aortic smooth muscle cells. For comparison, co-culture–seeded microchannels without breast cancer cells (MDAMB-negative) were fabricated. Results: After 7 and 14 days, the endoluminal lining of encapsulated MDAMB-231 co-culture–seeded microchannels demonstrated aberrant endothelial cell and smooth muscle cell organization and breast cancer cell transendothelial migration. MDAMB-231 cells performed matrix remodeling, forming tumor aggregates within the bulk, migrating preferentially toward the hydrogel "neovessel." In contrast, MDAMB-negative constructs demonstrated maintenance of an intact endoluminal lining composed of endothelial cells and smooth muscle cells that organized into discrete layers. Furthermore, the thicknesses of the endoluminal lining of MDAMB-negative constructs were significantly greater than encapsulated MDAMB-231 co-culture–seeded constructs after 7 and 14 days ( p = 0.012 and p < 0.001, respectively). Conclusion: The authors have created a powerful tool that may have tremendous impact on furthering our understanding of cancer recurrence and metastasis, shedding light on these poorly understood phenomena.